Características clínico epidemiológicas de las úlceras corneales bacterianas en el Instituto Regional de Oftalmologia Javier Servat Univazo - Cruz Valderrama, Eder Samuel (2020)
The purpose of the project is to describe the clinical-epidemiological characteristics of bacterial corneal ulcers in patients who attended the “Javier Servat Univaso” Regional Institute of Ophthalmology (IRO) in Trujillo. For this, the clinical history of patients treated at the IRO “JSU” during the period January 2009 to December 2019, who meet the following criteria will be evaluated: diagnosis of bacterial corneal ulcer by means of a positive culture filed or described in the clinical history, all ages and both sexes, whose data will go in the data collection sheets (annex 1). The data from the files will be entered in the statistical package Microsoft Office Excel 2018 and SPSS 20, for the presentation of data, frequency tables of one entry will be constructed, with absolute and relative values of the epidemiological profile such as area of residence, occupation, etiological agent , risk factors and clinical characteristics such as the affected area, size, depth, inflammatory reaction in the anterior chamber, visual acuity before and after treatment, medical management (monotherapy or fortified antibiotics), surgical management, treatment time, treatment time epithelialization, complications (corneal dellen, descemetocele and corneal perforation) and sequelae (leucoma, glaucoma and cataract).